1998
DOI: 10.1002/(sici)1521-4141(199805)28:05<1636::aid-immu1636>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of antigen between dendritic cells in the stimulation of primary T cell proliferation

Abstract: Primary proliferative T cell responses require stimulation with antigen-pulsed dendritic cells (Ag-DC). Here we show that for optimal stimulation, dendritic cells (DC) not exposed directly to antigen are also required. Ag-DC added to DC-depleted T cells caused negligible primary stimulation; adding back DC resulted in stimulation. These effects were seen using the contact sensitizer fluorescein isothiocyanate (FITC), FITC conjugated to ovalbumin (FITC-OVA) or influenza virus as antigens. DC co-cultured with Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 24 publications
(25 reference statements)
4
33
0
Order By: Relevance
“…The proportion of DCs presenting antigen may exceed this figure, partly because DCs expressing antigen genes at undetectable levels can stimulate antigen-specific T-cell responses 14 , and partly because antigen may be transferred readily from DCs producing it endogenously to other DCs (ref. 23). Our results with human DCs showed that CL22 transfection enabled the hmoDCs to stimulate in vitro expansion and activation of antigen-specific, autologous CD8 + T cells for recall antigens, allowing detection of their lytic activity on target cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of DCs presenting antigen may exceed this figure, partly because DCs expressing antigen genes at undetectable levels can stimulate antigen-specific T-cell responses 14 , and partly because antigen may be transferred readily from DCs producing it endogenously to other DCs (ref. 23). Our results with human DCs showed that CL22 transfection enabled the hmoDCs to stimulate in vitro expansion and activation of antigen-specific, autologous CD8 + T cells for recall antigens, allowing detection of their lytic activity on target cells.…”
Section: Discussionmentioning
confidence: 99%
“…To verify that any changes were independent of the antigen used, a different contact antigen (FITC) was used in separate experiments. The method used to conjugate FITC to APC in vitro was similar to that above and has been described elsewhere (Knight et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…49 It is likely that interdigitating dendritic cells are simply interstitial dendritic cells (see below) and Langerhans cells that have migrated to the lymph node from peripheral tissues and undergone maturation ( Figure 5), although some authors suggest that they may be a separate DC population to which antigen is passed by DCs migrating from peripheral tissues. 49,50 Interstitial dendritic cells and macrophages: prior to immunohistochemistry, the poorly defined term ''histiocyte'' referred to a cell with macrophage or epidermal Langerhans cell morphology. 10,40,51,52 Subsequently, ''histiocyte'' referred to cells that were CD68þ.…”
Section: Mast Cellsmentioning
confidence: 99%